Electrolyte‐gated organic field‐effect transistors with high operational stability and lifetime in practical electrolytes - Dimitrios Simatos; Mark Nikolka; Jérôme Charmet; Leszek J. Spalek; Zenon Toprakcioglu; Ian E. Jacobs; Ivan B. Dimov; Guillaume Schweicher; Mi Jung Lee; Carmen M. Fernández‐Posada; Duncan J. Howe; Tuuli A. Hakala; et al. (SmartMat)
Abstract A key component of organic bioelectronics is electrolyte‐gated organic field‐effect transistors (EG‐OFETs), which have recently been used as sensors to demonstrate label‐free, single‐molecule detection. However, these devices exhibit limited stability when operated in direct contact with aqueous electrolytes. Ultrahigh stability is demonstrated to be achievable through the utilization of a systematic multifactorial approach in this study. EG‐OFETs with operational stability and lifetime several orders of magnitude higher than the state of the art have been fabricated by carefully controlling a set of intricate stability‐limiting factors, including contamination and corrosion. The indacenodithiophene‐co‐benzothiadiazole (IDTBT) EG‐OFETs exhibit operational stability that exceeds 900 min in a variety of widely used electrolytes, with an overall lifetime exceeding 2 months in ultrapure water and 1 month in various electrolytes. The devices were not affected by electrical stress‐induced trap states and can remain stable even in voltage ranges where electrochemical doping occurs. To validate the applicability of our stabilized device for biosensing applications, the reliable detection of the protein lysozyme in ultrapure water and in a physiological sodium phosphate buffer solution for 1500 min was demonstrated. The results show that polymer‐based EG‐OFETs are a viable architecture not only for short‐term but also for long‐term biosensing applications.